Conservative Management of Invasive Cervical Resorption: A Case Report - Youssef Abdullah Algarni (Journal of Pharmacy and Bioallied Sciences)
“Invasive cervical resorption” (ICR) is a disorder that impacts the region of root surface that is present below the level of attachment of epithelium. Clinically, it manifests as a pink stain on the cervical part of the tooth. It may be due to visualization of the densely vascularized granular tissue across the resorbed structure of the tooth. The invasive defect should be made visible, the granulation tissue should be removed, and the defect should be sealed using a variety of restorative materials. In this report, a patient who presented with trauma related Class II ICR in the cervical region of the left second premolar of the maxilla was treated conservatively. It was shown that patients who are reluctant to undergo surgery or in whom surgery is not recommended could be treated with this conservative approach to stop the advancement of ICR.